Cardiovascular diseases, NLRP3 inflammasome, and western dietary patterns. (May 2018) - Pavillard, Luis E.; Marín-Aguilar, Fabiola; Bullon, Pedro; Cordero, Mario D.
Graphical abstract: Abstract: Cardiovascular diseases (CVD) are the leading cause of death worldwide, with high prevalence in industrialized countries. Cardiovascular risk factors are mainly influenced by diet, which like other lifestyle factors can be modified to either reduce or increase cardiovascular risk. Other metabolic diseases such as metabolic syndrome, type II diabetes mellitus, and obesity are associated to CVD and highly influenced by the diet. Inflammation has demonstrated to be a key factor in the biological progress of these diseases. Interestingly, IL-1β which is associated to several steps in the development of atherosclerosis, heart disease, and the association of obesity and type II diabetes with CVD, is activated by the inflammasome complex, a multiprotein complex composed of an intracellular sensor, typically a Nod-like receptor (NLR), the precursor procaspase-1, and the adaptor ASC (apoptosis-associated speck-like protein containing a CARD. In the last years, inflammasome complex has been studied in depth and has been associated with the effect of unhealthy diets both from a clinical and experimental view point. We have reviewed the evidences supporting the role of the inflammasome complex in the development of cardiovascular pathology by unhealthy diets and the therapeutic perspectives.